Highs School Students Perspective on Using Tiktok for Learning English Vocabulary - Wenny Catrin Tiara Sirait; Mahmud Layan Hutasuhut (Universitas Negeri Medan, 2023)
This study aims to answer the questions mentioned in the problems of the study, listed as follows: To formulate students’ perspectives of using TikTok as a means for learning English vocabulary, and to discover a significant difference on the perception of students both who use and who do not use TikTok when learning English vocabulary.The researcher used a mixed methods research design in order to to know the students' perspectives in year X at SMA Swasta Imelda Medan by sharing questionnaires and conducting interviews. The findings showed that the vast majority of students concurred with the statement that they interested to learn further English vocabulary via the TikTok application because the media is very user-friendly. They were able to imitate how words were pronounced in an accurate and satisfactory manner. The researcher concluded that using TikTok significantly impacts the students after considering the results and the discussion.. As a result, the method of increasing vocabulary in the tenth grade at SMA Swasta Imelda Medan could involve using the TikTok application.Keywords: Students’ Perspective, English Vocabulary, TikTok